2018
DOI: 10.1186/s40478-018-0568-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of tau in the human and rodent enteric nervous system under physiological conditions and in tauopathy

Abstract: Tau is normally a highly soluble phosphoprotein found predominantly in neurons. Six different isoforms of tau are expressed in the adult human CNS. Under pathological conditions, phosphorylated tau aggregates are a defining feature of neurodegenerative disorders called tauopathies. Recent findings have suggested a potential role of the gut-brain axis in CNS homeostasis, and therefore we set out to examine the isoform profile and phosphorylation state of tau in the enteric nervous system (ENS) under physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 67 publications
(100 reference statements)
10
61
0
Order By: Relevance
“…There were no correlations between the expression levels of tau, age and disease duration ( Figure S2). We have recently shown that 1N3R and 0N4R are the two main tau isoforms expressed in the adult human ENS and that these two isoforms are phosphorylated under physiological conditions (16). Using 3R and 4R isoform specific antibodies, we found that both 1N3R and 0N4R tau isoforms were upregulated in the inflamed area in CD ( Figure 1B).…”
Section: Tau Expression Is Increased In Crohn's Disease But Not In Ulmentioning
confidence: 71%
See 1 more Smart Citation
“…There were no correlations between the expression levels of tau, age and disease duration ( Figure S2). We have recently shown that 1N3R and 0N4R are the two main tau isoforms expressed in the adult human ENS and that these two isoforms are phosphorylated under physiological conditions (16). Using 3R and 4R isoform specific antibodies, we found that both 1N3R and 0N4R tau isoforms were upregulated in the inflamed area in CD ( Figure 1B).…”
Section: Tau Expression Is Increased In Crohn's Disease But Not In Ulmentioning
confidence: 71%
“…It should be noted however that the pathological distinction among these disorders is sometimes not so clear as the co-occurrence of alpha-synuclein and tau deposits has been reported in PD (12). Several independent studies have shown that enteric neurons, like their CNS counterparts, also express alpha-synuclein (13)(14)(15) and tau (16,17) and we recently demonstrated that alpha-synuclein is upregulated in inflamed segments of Crohn's colon (18). These latter findings, together with the results of recent epidemiological (19,20) and genetical studies (21), support the existence of a close relationship between Parkinson's and Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the isoform profile of tau differed between the ENS and the CNS, with 1N3R and 0N4R being the two main tau isoforms expressed in adult human enteric neurons (16). In addition, we did not observe any changes in tau expression, phosphorylation or truncation of colonic samples from patients suffering from the prototypical tauopathy progressive supranuclear palsy (PSP).…”
Section: Discussionmentioning
confidence: 82%
“…We first analyzed the expression levels of tau in colonic biopsies of CD and controls by Western are the two main tau isoforms expressed in the adult human ENS and that these two isoforms are phosphorylated under physiological conditions (16). Using 3R and 4R isoform specific antibodies, we found that both 1N3R and 0N4R tau isoforms were upregulated in the inflamed area in CD ( Figure 1b).…”
Section: Tau Expression Is Increased In Crohn's Disease But Not In Ulmentioning
confidence: 99%
See 1 more Smart Citation